2012
DOI: 10.1161/circulationaha.111.085811
|View full text |Cite
|
Sign up to set email alerts
|

Residential Proximity to Major Roadway and 10-Year All-Cause Mortality After Myocardial Infarction

Abstract: Background-The relationship between residential proximity to roadway and long-term survival after acute myocardial infarction (AMI) is unknown. We investigated the association between distance from residence and major roadway and 10-year all-cause mortality after AMI in the Determinants of Myocardial Infarction Onset Study (Onset Study), hypothesizing that living closer to a major roadway at the time of AMI would be associated with increased risk of mortality. Methods and Results-The Onset Study enrolled 3886 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 48 publications
5
42
1
Order By: Relevance
“…The strongest associations were observed among individuals living <100m of a high traffic road in categorical analysis and remained consistent with a log-linear association. Our findings are also consistent with the results of previous studies that have shown that living close to a major road is associated with higher mortality rate [1618]. …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The strongest associations were observed among individuals living <100m of a high traffic road in categorical analysis and remained consistent with a log-linear association. Our findings are also consistent with the results of previous studies that have shown that living close to a major road is associated with higher mortality rate [1618]. …”
Section: Discussionsupporting
confidence: 93%
“…Studies in other susceptible populations have shown that living near a major roadway is associated with all-cause mortality [19], cardiopulmonary mortality [20], post-myocardial infarction mortality [18], and deep vein thrombosis [21]. Evidence also suggest that there may be chronic effects of living in a location with higher exposure to air pollution, and one study in women found that living in close proximity to a roadway was also associated with elevated incidence of stroke (Hazard Ratio (HR) 2.08 (95%CI: 1.25, 3.48) and death from cerebrovascular disease (HR 2.93 (95%CI: 1.03, 8.38) [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…also found individuals living closer to a major roadway were more likely to be of non-White race/ethnicity. 44 Living in census tracts with higher percentages of Hispanics was associated with higher exposures to PM 2.5 and NO X , independently of individual race/ethnicity. These findings were largely consistent with a few previous studies of racial/ethnic composition and air pollution exposure.…”
Section: Discussionmentioning
confidence: 93%
“…We also tested the natural logarithm of the proximity to a major roadway and brachial function because it is associated linearly with mortality. 12 Participants living further than 1,000 m from a major road in rural areas beyond background were excluded from the roadway analyses (530 participants, 10%).…”
Section: Methodsmentioning
confidence: 99%